Diseño y modelación de una cabina de pintura aplicando criterios de producción más limpia (PML) para Talleres Maldonado, Parroquia La Magdalena, Cantón Quito, Provincia Pichincha - Guevara Zambrano, Luis Fabián (2016)
The present project addresses the problem of an automobile repair shop in relation to the design and simulation of a car paint booth due to the fact that this area is an important element in the development of the repair shop and the investment in its optimal design is highly relevant in terms of economic and energetic costs. First, this project encompasses all the theory related to environmental impact issues produced by automobile repair shops in order to provide a perspective about the general importance of the project. Therefore, it also addresses clean production implementation related to car paint booths at an international and local level. Furthermore, it becomes necessary to talk about the design. This section is about the characteristics of the company for which the project will be executed, the different restrictions present in the project and the definition of the alternatives of clean production for the paint booth. The features of the booth and the calculations for its optimal design will also be included in this section. In addition, the project also takes into account the thermic and dynamic simulation of the flow regimes using Solid Works to put in evidence all the characteristics that are necessary to operate the paint booth in a satisfactory way at the Maldonado workshop. Finally, the results obtained from the simulation will be analyzed and translated into recommendations and conclusions, which are deeply related to the objectives previously set out.